The Effectiveness of Mindfulness-Based Stress Reduction (MBSR) on the Posttraumatic Growth and the Psychological Capital in Women with Breast Cancer - Rahimi Cham Heydari , Razie; Mahmoud fakhe, Heman (Advances in Nursing & Midwifery, 2021)
Introduction: Breast cancer is known as the most prevalent type of cancer in the women around the globe. Cancer is a group of diseases which involving uncontrolled abnormal cell growth. Undergoing stress-provoking situations can lead to positive physical and psychological outcomes. Therefore, regarding the prevalence and importance of this condition, the current study aims to examine the effectiveness of the mindfulness-based stress reduction (MBSR) therapy on the posttraumatic growth and the psychological capital in women diagnosed with breast cancer. Method: The current investigation is a quasi-experimental study with pre-test and post-test assessments and experimental and control groups. The population of the study included all the women with breast cancer who had sought professional help in Imam Khomeini hospital (Tehran) since 2020. Among these individuals, 30 were selected using purposive sampling and afterwards were assigned to the control (15) and experimental (15) groups randomly. The conducted measurements included The Post Traumatic Growth Inventory (PTGI) (Tedeschi and Calhoun, 1996) and The Psychological Capital Questionnaire (PCQ) (Luthans, 2007). The data were analyzed using SPSS-23, descriptive statistics and inferential statistics (repeated measures ANOVA). Results: According to the findings, compared to the control group, the mindfulness-based stress reduction therapy affected the experimental group more significantly in terms of the posttraumatic growth and the psychological capital. The mentioned effects were maintained after a 1-month follow-up assessment. Conclusion: Regarding the mentioned results, MBSR could be considered as an effective therapeutic approach for increasing the posttraumatic growth and the psychological capital in women suffering from breast cancer.